2008
DOI: 10.4314/ari.v2i1.40844
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Exposure To Sublethal Concentrations Of Gammalin 20 And Actellic 25 Ec On The Liver And Serum Lactate Dehydrogenase Activity In The Fish Clarias Albopunctatus

Abstract: One hundred and eighty adult Clarias albopunctatus (mean weight 160±2.7g) were subjected to sublethal concentrations of Gammalin 20 and Actellic 25 EC (0, 0.3;and 1.0 µg/l) in a static bioassay renewal system for 18 days. The changes in the activities of the liver and serum lac ate dehydrogenase (LDH) during the period of exposure were studied. The exposure of C. albopunctatus to these pesticides evoked significant increase (P< 0.05) in both the liver and serum LDH activities. There was a progressive increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
2
5
1
Order By: Relevance
“…The result of our study indicated that the increases in SRA and HCA activity of H. bidorsalis juveniles were dependent on the BLCO concentrations to which the fishes were exposed (Table 2). This result is consistent with the report of Oluah et al (2005) who obtained increases in the serum and liver lactate dehydrogenase (LDH) activity in Clarias albopunctatus exposed to increasing concentrations of sublethal Gammalin 20 and Acetellic 25EC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The result of our study indicated that the increases in SRA and HCA activity of H. bidorsalis juveniles were dependent on the BLCO concentrations to which the fishes were exposed (Table 2). This result is consistent with the report of Oluah et al (2005) who obtained increases in the serum and liver lactate dehydrogenase (LDH) activity in Clarias albopunctatus exposed to increasing concentrations of sublethal Gammalin 20 and Acetellic 25EC.…”
Section: Discussionsupporting
confidence: 92%
“…The biochemical response of aquatic organism to pollution is given by changes several key enzymes, especially those of biotransformation systems. The value of tissue enzyme activities in the diagnosis of the effects of pollutant is an emerging area in aquatic toxicology and remediation programmes (Oluah et al, 2005). Thirugnanam and Forgash (1977) studied the anticholinesterase effect of chlorpyrifos to Fundulus heteroclistis and reported that increased concentration of the mosquito pesticides in salt water mash habitat resulted in maximum anticholinesterase inhibition in the fish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of liver injury is often dependent not only on the toxicant and its mechanism of action but also on the duration of exposure (Jacobson-Kram and Keller, 2006). Evaluation of enzyme activities in the tissues and organs of aquatic organisms in the diagnosis of the effects of pollutants is one of the emerging areas in toxicological monitoring and remediation programmes (Oluah et al, 2005). Fluctuations in aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities reflect liver damage (Bernet et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of enzymes activities in the tissue and organs of aquatic organisms in the diagnosis of the effects of pollutants is one of the emerging areas in toxicological monitoring and remediation (Oluah et al, 2005). Enzyme Activity is one major parameter used in assessing the early stage of pesticide toxicity (Duta and Areids, 2003).…”
Section: Introductionmentioning
confidence: 99%